The COVID-19 pandemic is one of the components of the multicomponent pandemic of the 21st century - GM Bushmanova; MV Supotnitsky (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Let us try to look at the "new" problem by the example of two "linked" pandemics, which are prepared for the possibility of coexistence in the 21st century. Today there can be no doubt the evidence of a significant age difference between the little-known COVID-19 that was born this year and that we have studied enough for a 40-year period (1980-2020), until the conscious medical community, primary chronic sepsis (P-ChS), associated with primary chronic septic endovasculitis, implemented in most cases in endocarditis (P-CSE) [1,2]